Bioactive constituents of Goniothalamus tamirensis essential oil and its anticancer activity - Nguyen, Khanh Thuy Linh; Doan, Quoc Tuan; Nguyen, Duy Co; Le, Duong Yen Nhi (Tạp chí Y Dược Huế, 2025)
Background and objectives: Cancer is a major challenge, affecting health, society, and the economy. Natural therapies may help reduce side effects of conventional treatment. The present study aimed to determine phytochemical characterization and evaluation of in vitro anticancer activity of the essential oil (EO) obtained from G. tamirensis leaves. Materials and methods: The leaves of G. tamirensis were collected in Phong Dien, Thua Thien Hue, in August 2024. The chemical composition of the EO was identified using GC-MS, and the anticancer potential of the EO was evaluated using the SRB assay against human cell lines (HepG2, MCF7, A549). Results: The main compounds identified in G. tamirensis EO were oxygenated sesquiterpenes. The EO showed significant anticancer activity against MCF, A549 and HepG2 cell lines with IC50 of 8.79, 10.29 and 7.32 mg/mL, respectively. Conclusion: This study suggests that G. tamirensis leaf EO is a promising candidate for use as an anticancer agent.